OCEANS 2019 - Marseille 2019
DOI: 10.1109/oceanse.2019.8867271
|View full text |Cite
|
Sign up to set email alerts
|

Detection strategy for long-term acoustic monitoring of blue whale stereotyped and non-stereotyped calls in the Southern Indian Ocean

Abstract: The most common approach to monitor mysticete acoustic presence is to detect and count their calls in audio records. To implement this method on large datasets, polyvalent and robust automated call detectors are required. Evaluating their performance is essential, to design a detection strategy adapted to study the available datasets. This assessment then enables accurate post-analyses and comparisons of multiple independent surveys. In this paper, we present the performance of a detector based on dictionaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 25 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…A threshold corresponding to one false positive detection per hour was set and the corresponding recall reached 90% for positive SNR calls (Torterotot et al, 2019). The detector was then tested on an entire year of data ( 2015) at WKER site and every detection was manually double checked, to characterize any interferences that could fool the algorithm and to re-evaluate the false alarm rate in case of call absence.…”
Section: Automated Call Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A threshold corresponding to one false positive detection per hour was set and the corresponding recall reached 90% for positive SNR calls (Torterotot et al, 2019). The detector was then tested on an entire year of data ( 2015) at WKER site and every detection was manually double checked, to characterize any interferences that could fool the algorithm and to re-evaluate the false alarm rate in case of call absence.…”
Section: Automated Call Detectionmentioning
confidence: 99%
“…The performance evaluation of the algorithm on the same data used in this paper is thoroughly discussed in Torterotot et al (2019).…”
Section: Automated Call Detectionmentioning
confidence: 99%
“…If the signal is well reconstructed by the linear combination of K elements among the dictionary's waveforms, then the resemblance metric is higher than the threshold measured empirically in Torterotot et al, (2019), meaning that it is likely that a D-call lays in the observed signal (Guilment et al, 2018;Socheleau et al, 2018). Before applying the SRD to detect D-calls on the whole data set, its performance was investigated on manually annotated data subsets containing 240.5 hr of recordings from different years and locations of the OHASISBIO data set (NEAMS 2015, SSWIR 2017, WKER 2015, and WKER 2012 with a total of 3,467 D-call annotations, to encompass potential temporal and geographical variation of the calls.…”
Section: Automated Call Detectionmentioning
confidence: 99%
“…Although visual examination of the data proved to be the most reliable technique to detect D-calls, we had to resort to a semiautomated detection method to process such a large amount of data. We selected an automated detection algorithm based on dictionary learning and sparse representation (Socheleau et al, 2018) and combined it with a postprocessing algorithm to reject false positives (Torterotot et al, 2019).…”
Section: Automated Call Detectionmentioning
confidence: 99%
“…To investigate the vocal repertoire of Southeast Alaskan humpback whales, three classification systems were used, including aural spectrogram analysis, statistical cluster analysis, and discriminant function analysis, to describe and classify vocalizations, and a hierarchical acoustic structure was identified to classify vocalizations into 16 individual call types nested within four vocal classes (Fournet et al, 2015). For blue whale signals in particular, most detection methods have been based on detection either in the time domain (e.g., matched filtering; Stafford et al, 1998) Socheleau et al, 2015;Torterotot et al, 2019).…”
Section: B Motivation For the Workmentioning
confidence: 99%